The Role of the Internal Audit Function in Detecting and Preventing Fraud at a South African Municipality - Mbetha, Sphokazi; Moosa, Riyad (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This study aimed to understand the role of the IAF in detecting and preventing fraud at a South African municipality in Gauteng. This study employed a qualitative approach based on the interpretivism paradigm, utilising a single case study. Participants were selected through purposive sampling, and the data were analysed using inductive analysis. The study found nine roles required by the municipality of their IAF for fraud detection and prevention. Seven of these roles align with the requirements of the standards, which means there is no expectation gap between the needs of the municipality and the standards. These roles are: 1) identification of fraud risks, 2) providing recommendations to management, 3) conducting fraud awareness sessions, 4) reporting to the audit committee, 5) evaluating internal controls, 6) exercising due professional care, and 7) planning for annual audits. In addition, two roles required by the municipality were found to contravene the requirements of the standards, namely 1) designing fraud detection and prevention controls and 2) conducting fraud investigations. These two roles indicate that there is an expectation gap. This study provided several recommendations to management and the municipality's accounting officer to reduce the expectation gap.